2022
DOI: 10.1103/physrevmaterials.6.044403
|View full text |Cite
|
Sign up to set email alerts
|

A room temperature polar magnetic metal

Abstract: The emergence of long-range magnetic order in non-centrosymmetric compounds has stimulated interest in the possibility of exotic spin transport phenomena and topologically protected spin textures for applications in next generation spintronics. Polar magnets, with broken symmetries of spatial inversion and time reversal, usually host chiral spin textures. This work reports a novel wurtzite-structure polar magnetic metal, identified as AA'-stacked (Fe 0.5 Co 0.5 ) 5 GeTe 2 , which exhibits a Néel-type skyrmion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 53 publications
1
35
0
Order By: Relevance
“…at ≈50%, the material becomes antiferromagnetic. We note that another work reports the realization of a polar ferromagnetic metal with 50% Co-substituted Fe5GeTe2 [31]. Difference between these two works may be due to minor differences in composition and the resulting structure.…”
Section: Characterization Of Bulk Cfgt Crystalmentioning
confidence: 86%
See 1 more Smart Citation
“…at ≈50%, the material becomes antiferromagnetic. We note that another work reports the realization of a polar ferromagnetic metal with 50% Co-substituted Fe5GeTe2 [31]. Difference between these two works may be due to minor differences in composition and the resulting structure.…”
Section: Characterization Of Bulk Cfgt Crystalmentioning
confidence: 86%
“…Material reported in Ref. [31] also exhibits a high Tc ≈350 K, but magnetic properties were only examined in flakes with thickness >100 nm. In the present work, all CFGT corresponds to the 28% Co-substituted crystals as reported in Ref.…”
Section: Characterization Of Bulk Cfgt Crystalmentioning
confidence: 99%
“…However, skyrmion phases can only exist in Cr 2 Ge 2 Te 6 and Fe 3 GeTe 2 at temperatures considerably lower than room temperature, which greatly limits their practical applications. Recently, Zhang et al [ 171 ] reported a 2D polar ferromagnet, (Fe 0.5 Co 0.5 ) 5− x GeTe 2 , with a Curie temperature of ≈350 K. Notably, Néel‐type skyrmions were observed in this material at room temperature. [ 172 ] The findings on room‐temperature skyrmions in 2D magnets pave the way for skyrmion‐based 2D IMDs.…”
Section: Imds: Mechanisms Architectures and Applicationsmentioning
confidence: 97%
“…An as-yet unexplored possibility for designing polar metals is to introduce magnetic spin spirals that break the inversion symmetry into metallic systems, analogous to the established spin-driven FE polarization in the prototypical type-II multiferroic, TbMnO 3 [84]. Although rare, several magnetic polar metals have already been reported [85][86][87][88]. Among these, interestingly, Fe-doped Ca 3 Ru 2 O 7 , Ca 3 (Ru 0.95 Fe 0.05 ) 2 O 7 , has an incommensurate spiral spin structure which resembles that of TbMnO 3 [85].…”
Section: Spin-spiral-driven Polar Metalsmentioning
confidence: 99%
“…While many interesting potentially useful properties of polar metals, such as, unconventional superconductivity [94], thermoelectricity [95,96], complex magnetism [85,88], multiferroicity [57], and nontrivial topology [97,98], have been realized, many proposed behaviors are yet to be uncovered. Here, we summarize some properties and potential applications that we find particularly promising for future investigation.…”
Section: Properties and Prospectsmentioning
confidence: 99%